On the numerical prediction of the anisotropic elastic properties in thin-walled structures made from short-fiber reinforced plastics1 - Altenbach, Holm; Naumenko, Konstantin; Pylypenko, Sergiy (Computer Assisted Methods in Engineering and Science, 2022)
The paper presents a model which allows to estimate the elastic properties of thin-walled structures manufactured by means of injection molding. The starting point is the numerical prediction of the microstructure of a short fiber reinforced composite induced during the filling stage of the manufacturing process. For this purpose the commercial program Moldflow Plastic Insight® (MPI) is used. The result of the filling simulation characterizing the fiber microstructure is a second rank orientation tensor. The elastic material properties after the processing are locally dependent on the orientational distribution of the fibers. The constitutive model is formulated by means of the orientational averaging for the given orientation tensor. The tensor of elastic material properties is computed and translated into the format suitable for the stress-strain analysis based on the ANSYS® finite element code. The influence of technological manufacture parameters on the microstructure and the elastic properties is discussed with the help of two examples a center-gated disk and a shell of revolution.